Correlation of Stature with Footprint of Bangladeshi Male Medical Students (Bangladesh Journal of Anatomy, 2015)
Context: Foot dimension has great use in anatomy, physiology, ergonomics, forensic science, plastic surgery, radiology, podiatry, archaeology, anthropology, nutrition science and diagnostic knowledge between patient and normal population. The data of foot dimensions of Bangladeshi male is essential for the anatomist for normative reference. Stature can be correlated with foot dimensions using different foot segments from footprints. This cross sectional analytic study was planned to determine the different dimensions of the footprint of the Bangladeshi males and to find out the correlation of stature with foot dimensions from footprint of male Bangladeshi medical students.Materials & Methods: Two hundred (200) male medical college students of 18-25 years of age were selected from different medical colleges of Dhaka city and their age was determined by their national ID cards. Stature was measured using a stadiometer. Both feet of the same individual were painted with ink with the help of the brush. After ensuring that toes and sole were inked properly, footprints were taken at the same time for both feet while the ink was still wet. Length of the different toes(t) were then measured in centimetre from the footprints using a Vernier digital caliper.Results: In the present study, significant differences were observed between T1, T2, T3, T4 and T5 lengths of right and left foot (P